Comparison of key enablers for the successful comercialization of bioinformatics products in Malaysia and Singapore - Nagaretham, Revathi; Mohd Shah, Mohamed Irwan Shah; Ahmad Dahlan, Abdul Rahman (Human Resource Management Academic Research Society, 2012)
Bioinformatics can be defined as collection, organization and analysis of large amount of biological data. The exploration of science and technology (S&T) is very important for the firm’s and country’s growth. Malaysia had started looking at bioinformatics in 1997 but with a controversial issue. In 1999 the link between bioinformatics and biotechnology in Malaysia that called Biotechnology and Bioinformatics network has been launched to produce community of bioinformatics developers who can develop tools to be used by the biologist. Bioinformatics was introduced in Singapore in 1992 with the focus on mirroring of data collection and sequence analysis application development. Bioinformatics in Singapore started to develop when National University of Singapore (NUS) took deeper research on Kleisli system in 1994. Research and development (R&D) is seen as a huge influence in Malaysia and Singapore economic growth. The reason is because successful product that been produce by R&D will gave greater impact on the country’s economy. Government funding aid, education system, government policies and commercialization management are some of the key enablers that can influence the quality of R&D products.